Floorplan sizing by linear programming approximation - Chen, Pinhong; Kuh, Ernest S. (37th Design Automation Conference, 2000, 2000)
In this paper, we present an approximation algorithm by linear programming (LP) for floorplan sizing problem. Given any topological constraints between blocks, we can formulate it as an LP problem with a cost function for the minimum bounding box area. Unlike slicing structures, this approach can handle any topological constraints as well as soft/hard/preplaced blocks, and timing constraints. Empirically, our method needs few iterations to find the optimum solution and shows one order of improvement over previous methods both in run time and capability to handle a larger problem size even on a very limited computing resource PC.